2021
DOI: 10.1186/s12891-021-04598-7
|View full text |Cite
|
Sign up to set email alerts
|

Norepinephrine modulates IL-1β-induced catabolic response of human chondrocytes

Abstract: Background The influence of the sympathetic nervous system (SNS) on metabolism of bone and cartilage expressing β-adrenergic receptors (AR) was suggested. Here, we investigated whether the SNS functions as a modulator of cartilage metabolism induced by interleukin-1beta (IL-1β). Methods Human articular chondrocytes and articular cartilage were collected from patients with osteoarthritis (OA). Chondrocyte monolayer and cartilage explant culture were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Previous studies have reported that IL-1β promotes the secretion of pro-inflammatory mediators and accelerates OA progression [ 32 ]. Therefore, many studies use IL-1β as the major stimulator for OA [ 33 35 ]. Herein, IL-1β was also employed to establish in vitro OA model.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that IL-1β promotes the secretion of pro-inflammatory mediators and accelerates OA progression [ 32 ]. Therefore, many studies use IL-1β as the major stimulator for OA [ 33 35 ]. Herein, IL-1β was also employed to establish in vitro OA model.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, elevated blood levels of NE most likely lead to defective bones via dysregulated adrenergic signaling in bones [17,40,41]. β2-adrenergic receptor-mediated signaling in response to the elevated NE inhibits bone formation and triggers RANKL-mediated osteoclastogenesis, thus increasing bone resorption.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings indicate that ‘IH stress’ elevates circulating NE levels, probably via an increased sympathetic transduction [ 40 , 41 ]. Thus, elevated blood levels of NE most likely lead to defective bones via dysregulated adrenergic signaling in bones [ 17 , 42 , 43 ]. β2-adrenergic receptor-mediated signaling in response to the elevated NE inhibits bone formation and triggers RANKL-mediated osteoclastogenesis, thus increasing bone resorption.…”
Section: Discussionmentioning
confidence: 99%